Development of smart solar tracking system - Zohari, Mohd Hakimi; Zainal Abidin, Muhammad Heidzer; Hussein, Lukman Iqbal; Mokhtar, Mohd Hezri (UTHM Publishing, 2020)
The project is to design an active solar tracking system which able to track the sunlight with the aid of light dependent resistor (LDR) as input sensor to read the intensity of sunlight. The solar tracking system uses platform as a base and it is moved by a servo motor as the platform needs to be moved towards the sunlight to get the optimum light. The solar tracking system is programmed by using microcontroller Arduino Uno as a main controller. After the setup of the hardware and program, the tracking motion of the tracking system has been implemented to track the sun based on sunlight direction. In this work, it is designed that the motion of the tracking system is depends on the value read by LDR. As a conclusion, the solar tracking system can increase the solar panels efficiency by keeping the solar panels perpendicular with sun’s position.